If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 2 = 5x + 1 Combine like terms: 4 + 2 = 6 6 = 5x + 1 Reorder the terms: 6 = 1 + 5x Solving 6 = 1 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 6 + -5x = 1 + 5x + -5x Combine like terms: 5x + -5x = 0 6 + -5x = 1 + 0 6 + -5x = 1 Add '-6' to each side of the equation. 6 + -6 + -5x = 1 + -6 Combine like terms: 6 + -6 = 0 0 + -5x = 1 + -6 -5x = 1 + -6 Combine like terms: 1 + -6 = -5 -5x = -5 Divide each side by '-5'. x = 1 Simplifying x = 1
| 5(m-3)=24 | | (x-5)(x+0)(x+7)=0 | | X/Y=-4/5 | | (15/10)^(1/4)-1 | | 8x+1=31 | | (b+16)(b-18)=0 | | 9-4(2x-1)-3x+2= | | 3x^4-21x^3+24x^2+23x-34=0 | | 20(7u-8v+3w)= | | 7z+2=-6 | | -7+2=6 | | 9x+16-6x=10-2x-19 | | 2p-3=p-5 | | 5a-16=25 | | v^2-10v+16= | | 4w-3x-y-5w+18x-7y= | | -6+[25+(-12)]=43 | | X^2+100+60-3x+30-4x=180 | | -6+[25+(-12)]=31 | | -13+2x=-52+13 | | -6+[25+(-12)]=7 | | -6+[25+(-12)]=19 | | 4=5+2x | | 5x+17-4x=-2-10 | | X/Y=7/11 | | 3x^2-(3m-2)x-(3m+1)=0 | | 1/3*1/3*1/3*1/3*a*a*b*b*c | | 5x-3y=106 | | 16+7yi=8x+i | | x-6=3(2x) | | f-5-3f=7 | | 2x+(x+1)=2 |